Gross motor coordination and their relationship with body mass and physical activity level during growth in Children aged 8–11 years old: a longitudinal and allometric approach - Giuriato,Matteo; Lovecchio,Nicola; Carnevale Pellino,Vittoria; Mieszkowski,Jan; Kawczyński,Adam; Nevill,Alan; Biino,Valentina (PeerJ, 2022)
Background Gross motor coordination (GMC) is fundamental to the harmonious development of physical skills during the growth of children. This research aimed to explore the developmental changes in GMC during childhood, having controlled for the differences in children’s body size and shape using a longitudinal, allometric scaling methodology. Methods A total of 104 children from North-East Italy of third-fourth- and fifth-grade students and each participant were tested for three consequently years. Subjects performed the short version of korperkoordinationstest fur kinder (KTK3) and the anthropometric characteristics were simultaneously collected. The physical activity questionnaire (PAQ-C) was used to evaluate the weekly physical engagement. Results Ontogenetic multiplicative models suggested nonlinear associations with GMC across the children’s developmental years. Linear physique was a significant predictor associated with the development of GMC across time. PAQ-C was significantly associated with GMC from 8 to 13 years old. Conclusion Growth does not respect linear trends. A greater lean body mass could be assessed as a reliable predictor of GMC in children. The crucial period of life to improve the GMC is 8–10 years, while stabilization becomes evident from 10 to 13 years.
Keywords: Children; Allometric approach; Multilevel modeling; Physical activity level